Performance investigations on integrated MMF/FSO transmission enabled by OAM beams - Mehtab Singh; Somia A. Abd El-Mottaleb; Syed Alwee Aljunid; Hassan Yousif Ahmed; Medien Zeghid; Kottakkaran Sooppy Nisar (Results in Physics, 2023)
This paper introduces a new hybrid system for high-bandwidth and high-transmission-capacity communication. The system integrates a multi-mode fiber (MMF) cable with free space optics (FSO) using orbital angular momentum (OAM) multiplexing. The proposed system uses a single wavelength to simultaneously transmit 40 Gb/s data on four distinct OAM beams ((LG0,0, LG0,17, LG0,40, and LG0,75)) with a symmetric circular shape. The performance of the system was evaluated with a fixed MMF length of 100 m and varying FSO ranges, according to extreme climate changes such as rain and fog, and atmospheric turbulences. The results indicate that the suggested system is capable of transmit up to 1250 m (100 m MMF length + 1150 m FSO range) under clear weather (CW) and weak turbulence (WT), with a minimum transmission distance of 440 m (100 m MMF length + 340 m FSO range) under heavy fog (HF). The performance of the system was also demonstrated based on actual meteorological data for two different cities, Alexandria, Egypt and Chandigarh, India, with different visibility ranges and geographical locations. Since Alexandria has a longer visibility range than Chandigarh, our proposed model could spread over a larger area than it could be in Chandigarh. The obtained ranges were within an acceptable bit error rate (BER) of less than 10−9. The system’s maximum range was 1200 m for Alexandria and 1100 m for Chandigarh. The proposed model can be suggested for use in next generation (NG) passive optical networks (PON) for supporting symmetric 40 Gb/s data.